Review of current developments in microgravity-enabled rocket propulsion control devices - Zahaievskyi, Lev; Sanin, Anatolii (Challenges and Issues of Modern Science, 2023)
The flight of a spacecraft is characterized by the alternating change of active and passive segments of the trajectory. In the passive segments of the trajectory, the liquid fuel in the spacecraft tanks is in a state of reduced or zero gravity. In this case, the liquid-gas interface is distorted by the shape of the tank and the balance of forces on the free surface. During the passive segment of the flight, the spacecraft is subject to various forces:- Aerodynamic forces;- Light pressure;- Gravitational anomalies;- Small accelerations (caused by the operation of orientation engines of the spacecraft in space).When operating the main rocket engine, these forces can be ignored. However, in the passive segments of the trajectory, the fuel in the fuel tanks is capable of moving in any direction relative to the intake device under the influence of even such insignificant factors. It is also possible that the vapor phase may enter the main line, which will prevent the engine from restarting. In addition, fuel components can mix with the bleed gas under strong sloshing, which will disrupt the integrity and practicality of the fuel.There is a need to control the position of the fuel so that some part of the components is always close to the intake device and free from bleed gases. Therefore, it is necessary to install systems for controlling the position and ensuring the cleanliness of the fuel from the gas phase in zero gravity and during spacecraft thrust reversal.These systems are subdivided by the type of control forces into:- Mechanical;- Inertial;- Surface tension;- Electrostatic.